Kandungan Senyawa Fitokimia dan Aktivitas Antibakteri Ekstrak Daun Pepaya (Carica Papaya L.): Narrative Review - Umniyah Tsabitah Zahrani; Ihsanti Dwi Rahayu; Atri Sri Ulandari; Ramadhan Triyandi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
This narrative review article explores the potential of papaya leaves (Carica papaya L.) as an alternative antibacterial treatment due to the increasing problem of antibiotic resistance. Papaya leaves, commonly found in Indonesia, are known to have various pharmacological properties, including antibacterial effects. The article aims to collect and review existing literature on the phytochemical compounds and antibacterial activity of papaya leaf extract. Literature searches were conducted across several databases such as Google Scholar, NCBI, ResearchGate, and ScienceDirect using keywords like "antibacterial," "phytochemical screening," and "Carica papaya leaf." Articles from the last five years that were accessible in full text and relevant to the topic were selected, leading to the inclusion of 18 articles in the review.The findings indicate that papaya leaf extracts exhibit antibacterial properties against both gram-positive and gram-negative bacteria. The degree of antibacterial activity varies, ranging from weak to very strong inhibition. This antibacterial effect is attributed to the secondary metabolite compounds present in papaya leaves, including alkaloids, flavonoids, saponins, tannins, phenolics, terpenoids, and steroids. These compounds contribute to the biological activity of the extract, making it a promising candidate for further development as a natural antibacterial agent. Overall, this review underscores the importance of exploring medicinal plants like papaya leaves as viable alternatives to combat bacterial infections and address the growing issue of antibiotic resistance..